Implementasi Model Pendidikan Non Formal Berbasis Ketrampilan Agribisnis di Pusat Kegiatan Belajar Masyarakat (PKBM) Gita Gemilang dan PKBM Sukarakyat Kabupaten Garut - Rosmaladewi, Okke; Robana, Rubi; Irmawatie, Lilis (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2017)
Socio-economic conditions in a community of Pasirwangi subdistrict is an agricultural area with the majority of the population generally as low-educated peasants. The education they had were only as students of elementary school and even the Dropped-Outs. They live below the poverty line. The problem dimensions of poverty dominantly occurs in the area concerning economic issues, education and health. One of the attempts to parse the poverty circle is by a means of giving Non-Formal Education (PNF) which is suitable with the condition of the target community. The management of PNF itself is implemented by PKBM . It is established and run by community leaders who are concerned about the condition of the surroundings. PKBM management and learning implemented generally yet refers to a standard quality that has been set. Learning undertaken is to prepare for the equality test only. During this time, there are no skills given to learners. This makes PNF even worse. Thus, based on these conditions, PNF model agribusiness skills-based is one of the alternatives to improve the education quality and family productivity of the peasants. The purpose of this research is to solve the problems of quality improvement on the PNF as well as to increase society’s welfare. The results can be utilized for the benefit of both society and the institutions of PNF, e.g. PKBM. The program implementation strategy is a social engineering through multi-stakeholder partnership for improving PNF quality based on partnership principles, PKBM empowerment and active participation from stakeholders in a sustainable manner.